Competitiveness of Indonesian Shrimp Compare with Thailand Shrimp in Export Market - Lina Asmara Wati; Wen-I Chang; Mochammad Muslich Mustadjab (Wacana Journal of Social and Humanity Studies, 2013)
With the water area accounts for 81 percent of the total area, fishery is a major business in Indonesia. As one of the world's largest shrimp exporting countries, Indonesia also relies on the revenues of shrimp exports in the international markets. This research compared the competitiveness of shrimp export from Indonesia and Thailand to Japan and US. The indicator adopted in this research was the RCA index. In this research collected secondary data from 1989 to 2010 for analysis. Results showed RCA values of Indonesia were higher than 1, which indicates advantaged competitiveness of Indonesia shrimp exports in the liberalized markets. Nevertheless, compared with Thailand, Indonesia remained relatively disadvantaged. To reinforce the Indonesian shrimp export, necessary infrastructure, such as networks shipment or delivery, packaging and transportation, must be improved. Further researches to determine the factors affecting competitiveness of export shrimp in liberalized market, make and analyze for the policy strategy formulation of Indonesia shrimp export in liberalized market are also advised.Keywords: Competitiveness; Indonesian Shrimp Export; RCA.